Difference of the Gas Density Histograms in and out of spiral arms in Milky Way Galaxy. Issue Volume 14:Issue S345(2019) (August 2018) - Handa, Toshihiro; Maebata, Miru; Murase, Takeru; Fujita, Shinji; Kohno, Mikito; Kuno, Nario; Kuriki, Mika; Matsuo, Mitsuhiro; Minamidani, Tetsuhiro; Nishimura, Atsushi; Torii, Kazufumi; Tsuda, Yuya; et al.
Abstract: "Gas Density Histogram (GDH)" is an observational counterpart of the probability density function (PDF) of the gas density of interstellar medium (ISM). We used 12 CO data in ( l, b ) = (29°, 0) region from "FOREST unbiased galactic imaging survey with Nobeyama 45-m telescope (FUGIN)", which is a large coverage survey in three CO (1-0) lines. Using the kinetic distance, we estimated the volume density of the voxel from the observed column density. The resultant GDHs of the inter-arm regions show lognormal or lognormal-like, but those in the spiral arm regions show flat-top shape.